2015
DOI: 10.1016/j.surfcoat.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and diffusion processes during annealing of TiSi(V)N films

Abstract: The degradation of self-lubricant hard coatings applied in tools for high-speed cutting or dry drilling operations occurs by a combination of wear, oxidation and diffusion. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…At the same time, the introduction of gold into the oxide layer changed the surface phase constituents and improved the mechanical properties, and therefore it is worthwhile to discuss the mechanism of the pre-deposited gold in the CCT of titanium alloys. Thanks to the high a nity of Ti for O, the oxidation of titanium alloys is dominated by the inward diffusion of O 2− and the outward diffusion of Ti 4+ [19]. In our previous study, we found that with the existence of a gold layer on the surface of the titanium alloy, the outward diffusion of Ti ions is promoted to provide more fresh titanium atoms to react with oxygen [12].…”
Section: : Discussionmentioning
confidence: 98%
“…At the same time, the introduction of gold into the oxide layer changed the surface phase constituents and improved the mechanical properties, and therefore it is worthwhile to discuss the mechanism of the pre-deposited gold in the CCT of titanium alloys. Thanks to the high a nity of Ti for O, the oxidation of titanium alloys is dominated by the inward diffusion of O 2− and the outward diffusion of Ti 4+ [19]. In our previous study, we found that with the existence of a gold layer on the surface of the titanium alloy, the outward diffusion of Ti ions is promoted to provide more fresh titanium atoms to react with oxygen [12].…”
Section: : Discussionmentioning
confidence: 98%
“…They found that the coating degradation mechanism when exposed to 650 • C in a pure steam environment is adverse diffusion of the substrate elements and oxygen through coating growth defects or cracks formed due to thermal expansion coefficient mismatch between the coating and the substrate. Fernades et al [92] also demonstrated that the oxidation of TiSiVN coatings is controlled by the formation of a silicon oxide diffusion barrier which is affected by nodular defects in the as-deposited film. At nodular defects a complex oxide structure was developed.…”
Section: Oxidation Resistancementioning
confidence: 99%
“…The hardened zone under the oxide layer for CCT at 620 • C for 80 h was clearly deeper than that treated for 8 h. This suggested that vanadium only influenced the growth of the oxide layer or the oxygen diffusion in the oxide layer, but did not affect the oxygen diffusion in the substrate. Another impact of vanadium may be attributed to the high solubility of V in the titanium substrate, which facilitated the formation of the Ti(V)O 2 solid solution [21]. The V 3+ ion may replace the position of Ti 4+ ions to produce V-doped TiO 2 , increasing the interstitial Ti 4+ ion content and decreasing the excess electron content to accelerate oxidation.…”
Section: Oxidation Mechanism Of Titanium With Vanadiummentioning
confidence: 99%